Neospora caninum causes severe economic losses in cattle in the humid pampa region of Argentina - Moore, Prando Dadin (2013)
This work estimates the economic losses due to Neospora abortions in the humid pampa region of Argentina. The total dairy and beef cattle population at risk of abortion is 1,771,326 and 9,726,684 head, respectively. In dairy cattle, there was an 8 % risk of experiencing abortion due to a variety of causes, but 16.5 % of them were due to Neospora caninum. The economic losses were estimated at US$1,865 (range, 1,400–2,331) per abortion, which equates to a total loss of US$43,607,430 (range, 15,622,600–194,412,390) for the dairy industry at the humid pampa region of Argentina. In beef cattle, the overall risk of abortion was estimated to be 4.5 % for all pregnancies, whereas 6.7 % are specifically due to N. caninum, with an economic loss of US$440 (range, 150–730) per abortion. This amounts to an annual loss to the beef industry of US$12,903,440 (range, 1,130,700–42,070,630) in the same area. The results of this study show that Neospora infections and thus abortions cause severe economic impacts in the dairy and beef industries in the humid pampa region of Argentina, which is one the most important areas of cattle production in the world.